Enhancing Dietary Knowledge And Low-Salt Compliance In Hypertension Patients Through Flip Chart-Based Nutritional Literacy - Zahara, Ayu; Simbolon, Demsa; Yunita, Yunita (Jurnal Riset Kesehatan, 2024)
Hypertension is a non-communicable disease where blood pressure is above the normal limit, namely systolic â‰¥140 mmHg and diastolic â‰¥90 mmHg. Hypertension is often known as the "silent killer" because it has no symptoms. This research aims to determine the effect of nutritional literacy through flipchart media on knowledge and adherence to a low-salt diet in hypertension sufferers. This research is quantitative with a quasi-experimental design with a Pretest-Posttest Control Group Design approach. The intervention group was given nutritional literacy through flipchart media and the control group was only given leaflets. The results show a difference in the average post-test knowledge score between the intervention and control groups (p-value 0.000) and a difference in the average score for increasing sodium intake between the intervention group and the control group (p-value 0.017). After nutrition education with flipchart media, there was a difference in knowledge and salt intake between the intervention and control groups. The intervention group achieved higher knowledge and lower salt intake than the control group (p-value < 0.05).